Pembelajaran Daring Melalui Teknik Kolaboratif pada Keterampilan Menulis Peserta didik di SMA Darul Qur’an Kota Mojokerto - Umamah, Maftuhatul; Muassomah, Muassomah (Departemen Pendidikan Bahasa Arab, 2020)
This study explores online learning implementation using collaborative techniques on writing skill students at Darul Quran Senior High School, Mojokerto. This study uses descriptive qualitative methods with three data collection techniques: observation, interviews, and documentation. This study's results reveal several steps used by the teacher, namely: first, the teacher explains the basic competencies, materials, indicators, and learning objectives. Second, the teacher uploads the video into the Google classroom, and the students focus on recording the things contained in the video. Third, students are divided into several groups to discuss what was shown in the video and create it according to their creativity. Fourth, students conclude the learning material studied and provide responses and appreciation to students who have shown an increased attitude of cooperation and discipline during the learning process. Finally, collaborative techniques can invite students to be active, build cooperation, and feel confident in completing writing skill material tasks.